Political Institutions and Sorting in a Tiebout Model - Kollman, Ken; Miller, John H.; Page, Scott E. (American Economic Review, 1997)
We construct a computational model of Tiebout competition and show that political institutions differ in their ability to sort citizens effectively. In particular, we find that certain types of institutions–those that become more "politically unstable" as citizen heterogeneity increases–perform relatively poorly given a single jurisdiction, yet these same institutions perform relatively well when there are multiple jurisdictions. We provide an explanation for this phenomenon which draws upon simulated annealing, a discrete nonlinear search algorithm.